Geoid Determination In Uganda: Current Status - Ssengendo, Ronald; Sjöberg, Lars.E.; Gidudu, Anthony (Advances in Engineering and Technology, 2017)
Many professionals e.g. surveyors, engineers and GIS specialists are increasingly using Global Positioning System (GPS) or some other Global Navigation Satellite Systems (GNSS) for positioning and navigation. One of the greatest advantages of GPS is its ability to provide three-dimensional coordinates (latitude, longitude and height) anywhere in the world, any time irrespective of the weather. The GPS latitude and longitude can easily be transformed from the WGS84 reference system to a local reference (e.g. Arc 1960). However the GPSdetermined heights, i.e. ellipsoidal heights, are geometrical heights which have no physical meaning and therefore cannot be used in surveying and engineering projects. Their conversion to more meaningful orthometric heights require knowledge of the geoidal undulations, which can be determined from high resolution geoid models. Its absence in Uganda means that the full potential of GPS cannot be fully realized. This paper gives an overview of the need for an accurate geoid model in Uganda, the current status of the geodetic network in Uganda and different methods of geoid determination. Pending further investigation, preliminary findings indicate that in Uganda, the EGM2008 is the best geoid modal for GPS/leveling projects.
Keywords: Geoid model; Global Positioning System; Orthometric heights